How the changes in the key interest rates for the euro area affected European System of Central banks - Velická, Karin; Fleischmann, Luboš, 1969-; Vyletelka, Michal; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This paper examines the impact of changes in key interest rates in the Eurozone on Slovakia, which is part of the Eurozone, and the Czech Republic, which is not. Specifically, the analysis focuses on the financial statements of the European Central Bank (ECB) and the inflation and interest rates of Central European countries in 2022. The paper primarily uses data from the ECB's Annual Accounts of 2022 and the ECB’s Statistical Data Warehouse, analysing the data using MS Excel. The analysis explores the relationship between changes in the ECB's financial statements and key interest rates, as well as other economic factors such as the performance of the US dollar and the development of Euro bond yields and US Treasury bills. The paper also examines the impact of the ECB's monetary policy decisions on the Central European economies, particularly in response to rising inflation in the European Union. The main finding of this paper is that, in times of crisis, it is advantageous for countries to stand together as a union rather than addressing challenges individually. The consequences of individual approaches can be more severe for the economy.
Vedoucí práce: Luboš Fleischmann
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses